2020
DOI: 10.25248/reas.e4663.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados paliativos em pacientes oncológicos: uma abordagem do conhecimento dos enfermeiros

Abstract: Objetivo: Analisar o conhecimento dos profissionais enfermeiros acerca dos Cuidados Paliativos em pacientes oncológicos. Métodos: Estudo exploratório, observacional, de abordagem qualitativa, obtendo como participantes da pesquisa 17 enfermeiros que atuam na assistência de pacientes oncológicos. A coleta de dados ocorreu em novembro a dezembro de 2018, mediante questionário não estruturado. Resultados: Os dados foram analisados por intermédio da Grelha de Análise de Bardin e emergiram-se 4 categorias temáticas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Despite recognizing the importance of PC in pediatrics, this study evidenced the lack of knowledge on the subject and the fragility of training strategies available at this service. These results agree with other studies that demonstrated the lack of specific training on PC, and the knowledge by professionals working in this area is mainly related to professional experiences and personal initiatives [11][12][13][14] . A study carried out with 37 health professionals from a pediatric intensive care unit involving a nursing team, physicians, and physical therapists showed that the participants were not prepared to care for the patient under PC due to a lack of knowledge, inadequate training, lack of uniformity in assistance, and little involvement of the multidisciplinary team 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Despite recognizing the importance of PC in pediatrics, this study evidenced the lack of knowledge on the subject and the fragility of training strategies available at this service. These results agree with other studies that demonstrated the lack of specific training on PC, and the knowledge by professionals working in this area is mainly related to professional experiences and personal initiatives [11][12][13][14] . A study carried out with 37 health professionals from a pediatric intensive care unit involving a nursing team, physicians, and physical therapists showed that the participants were not prepared to care for the patient under PC due to a lack of knowledge, inadequate training, lack of uniformity in assistance, and little involvement of the multidisciplinary team 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Uma forma facilitadora de enfrentar este sofrimento e fortalecer a tríade profissionalpaciente -família que é um elo que se desenvolve através da comunicação interpessoal facilitando que a equipe interdisciplinar exerça funções que melhoram a qualidade de vida do paciente e de seus familiares, pois vários aspectos serão atendidos desde os físicos até os espirituais de forma holística contribuindo para que haja um alivio maior nos sintomas e no desconforto ocasionado pela doença (ARAÚJO et al, 2020).…”
Section: Introductionunclassified
“…Dessa forma, clientes oncológicos em cuidados paliativos necessitam de um suporte interdisciplinar que preze pela assistência ativa e integral, a qual seja pautada na humanização e individualidade, onde o cuidado se torna essencial para o alívio de desconfortos gerados pelos desgastes causado pelo câncer, já que o indivíduo pode até estar fora de possibilidade de cura, mas nunca estará de cuidado (Santos, Lira & Costa, 2018;Araújo et al, 2020).…”
Section: Introductionunclassified